EFEKTIVITAS LAYANAN INFORMASI DALAM MENANGGULANGI KENAKALAN REMAJA SISWA KELAS VIII SMP NEGERI 1 FANAYAMA - Fau, Sesilianus (Institut Pendidikan Tapanuli Selatan, 2018)
This research was grounded by the variety of juvenile delinquency data at SMP Negeri 1 Fanayama and the weaknesses of Guidance and Counseling teacher in providing information services for students. The purposes of this research were 1) to describe the degree of juvenile delinquency of eighth grade students of SMP Negeri 1 Fanayama before they were given information services, 2) to describe the degree of juvenile delinquency of eighth grade students of SMP Negeri 1 Fanayama after they were given information services, 3) to test the effectiveness of information services to cope with juvenile delinquency of eighth students of SMP Negeri 1 Fanayama. This research was a pre-experimental research and conducted by using the one-group pretest-posttest design. The population and sample were eighth grade students of SMP Negeri 1 Fanayama. The instrument of this research was questionnaire, and the data were analysed by using Wilcoxon signed ranks test. Based on the data of this research, it was found that 1) the average percentage of juvenile delinquency of eighth grade students of SMP Negeri 1 Fanayama before they were given information services was in high level (68.04%) with average score 85.05, 2) the average percentage of juvenile delinquency of eighth grade students of SMP Negeri 1 Fanayama after they were given information services was in low level (50.98%) with average score 63.73, 3) there was a significant difference between the degree of delinquency of eighth grade students of SMP Negeri 1 Fanayama before and after they were given information services. The H0 hypothesis was rejected, and Ha was accepted, which means information services were effective to cope with juvenile delinquency. Based on the research finding and data obtained, it is suggested to the head master of the school to provide time for the teacher of Guidance and Counseling to teach in the classroom in order to make the teacher gets deep information related to the student characters, so that he/she is able to prevent the juvenile delinquency of students at SMP Negeri 1 Fanayama. It is also suggested to the students of SMP Negeri 1 Fanayama to be more enthusiastic to receive Guidance and Counseling services in the school and to be more honest to the Guidance and Counseling when the face some problems.